Spreading depolarizations exhaust neuronal ATP in a model of cerebral ischemia - Karl Schoknecht; Felipe Baeza-Lehnert; Johannes Hirrlinger; Jens P. Dreier; Jens Eilers (Proceedings of the National Academy of Sciences, 2025)
Spreading depolarizations (SDs) have been identified in various brain pathologies. SDs increase the cerebral energy demand and, concomitantly, oxygen consumption, which indicates enhanced synthesis of adenosine triphosphate (ATP) by oxidative phosphorylation. Therefore, SDs are considered particularly detrimental during reduced supply of oxygen and glucose. However, measurements of intracellular neuronal ATP ([ATP] i ), ultimately reporting the balance of ATP synthesis and consumption during SDs, have not yet been conducted. Here, we investigated neuronal ATP homeostasis during SDs using two-photon imaging in acute brain slices from adult mice expressing the ATP sensor ATeam1.03 YEMK in neurons. SDs were induced by application of potassium chloride or by oxygen and glucose deprivation (OGD) and detected by recording the local field potential, extracellular potassium, as well as the intrinsic optical signal. We found that, in the presence of oxygen and glucose, SDs were accompanied by a substantial but transient drop in neuronal ATP sensor signals, corresponding to a drop in ATP. OGD, which prior to SDs was accompanied by only a slight reduction in ATP signals, led to a large, terminal drop in ATP signals during SDs. Subsequently, we investigated whether neurons could still regenerate ATP if oxygen and glucose were promptly resupplied following SD detection, and show that ATP depletion was essentially reversible in most cells. Our findings indicate that SDs are accompanied by a substantial increase in ATP consumption beyond production. This, under conditions that mimic reduced blood supply, leads to a breakdown of [ATP] i . Therefore, our findings support therapeutic strategies targeting SDs after cerebral ischemia.